Jan Patocka and the heritage of phenomenology centenary papers - Abrams, Erika; Chvatík, Ivan.; SpringerLink (Online service). (Dordrecht Netherlands Springer, 2011)
Whereas for the wider public Jan Patočka is known mainly through the circumstances of his death in Prague, on March 13, 1977, after long interrogations by the Communist secret police, as a defender of human and civic rights in Czechoslovakia and one of the first spokespersons of the Charter 77 movement, the international philosophical community sees in him an important and inspiring thinker, who elaborated in an original way the great wellsprings and impulses of European thought mainly Husserl's phenomenology and Heidegger's philosophy of existence. Patočka also reflected on the future of humanity in a globalized world and laid the foundations of an original philosophy of history. His work is a subject of lively philosophical discussion especially in French and German-speaking countries, but also, more recently, in the Hispanic world, North America and the Far East. In April 2007 scholars interested in Patočka's philosophy gathered in Prague from around the world to commemorate his centenary and the thirtieth anniversary of his death. The conference explored the significance of his work and its growing influence on contemporary philosophy. This volume presents in English language selected papers from the centenary conference. - Publisher's description.
Ivan Chvatík, Preface; Václav Havel, Remembering Jan Patocka; Miroslav Petrícek, Jan Patocka: Phenomenological Philosophy Today; Petr Pithart, Questioning as a Prerequisite for a Meaningful Protest; Martin Palou?, Jan Patocka?s Socratic Message for the 21st Century; Marc Crepon, Fear, Courage, Anger: the Socratic Lesson; Josef Moural (Prague): Time and Responsibility, Kwok-ying Lau, Patocka?s Concept of Europe: an Intercultural Consideration; Steven Crowell, Idealities of Nature: Jan Patocka on Reflection and the Three Movements of Human Life, Eddo Evink, The Relevance of Patocka's Negative Platonism; Burt Hopkins, Patocka's Phenomenological Appropriation of Plato; Renaud Barbaras, Phenomenology and Henology; Tamás Ullmann, Negative Platonism and the Problem of Appearance; Pierre Rodrigo, Negative Platonism and Maximal Existence in the thought of Jan Patocka; Johann Arnason, Negative Platonism: Between the History of Philosophy and the Philosophy of History; James Mensch, Patocka and Artificial Intelligence; Domenico Jervolino, Reading Patocka, in search for a philosophy of translation; Ludger Hagedorn, Beyond Myth and Enlightenment; Marcia Schuback, Sacrifice and Salvation: Jan Patocka's readings of Heidegger concerning the question of technique; Lubica Ucník, Patocka on Techno-Power and the Sacrificial Victim (Obet); James Dodd, The 20th Century as War
Electronic reproduction.
Keywords: Patocka, Jan -- 1907-1977.; Phenomenology; Literature -- Philosophy; Electronic books